Use of Mulches in Estblishment and Growth of Tree Species on Dry Lands - Singh, Balvinder; Gupta, G. N.; Prasad, K. G.; Mohan, S. (Indian Forester, 1988)
Field experiments at three locations, namely Bolampatti, Pethikuttai and Coimbatore (Coimbatore Forest Division, Tamil Nadu) having different rainfall pattern and soils were conducted in 1985-86. Coir pith mulch was used on heavier soils of Bolampatti and Coimbatore, while gravel mulch was used on medium soil of Pethikuttai. Height of A. planifrons (113%), A. nilotica (96%), P. pterocarpum (85%), A. indica (60%) and E. camaldulensis (57%) increased due to coir pith mulch treatment. Response to mulch treatment was not so marked in case of A. leucophloea (27%) and T. indica (13%). A. lebeek, E. cuminii and P. pinnata did not respond to treatment. At Pethikuttai, use of gravel mulch increased height of E. camaldulensis (53%), A. indica (59%) C. pentendra (47%), A. leucophloea (68%) and A. nilotica (96%), A. planifrons (51%), P. pterocarpum (91%) A. lebbeck (122%). Growth of E. cuminii, C. equisetifolia, P. pinnata and T. indica was not significant due to mulch. At Coimbalore, where additional water was also given during severe moisture stress, plant height of C. equisetifolia increased from 115 to 147 cm E. camaldulensis from 102 to 120 cm in 6 months after planting. T. indica did not respond to mulch application at this site. Use of coir pith mulch maintained significantly higher moisture regime at all the locations throughout the growth period. Coir pith mulch reduced the surface soil temperature by 3 to 5Â°C at Coimbatore.